2017
DOI: 10.1007/s13337-016-0358-0
|View full text |Cite
|
Sign up to set email alerts
|

Emerging threats of begomoviruses to the cultivation of medicinal and aromatic crops and their management strategies

Abstract: Begomoviruses (family Geminiviridae) are responsible for extreme yield reduction in a number of economically important crops including medicinal and aromatic plants (MAPs). Emergence of new variants of viruses due to recombination and mutations in the genomes, modern cropping systems, introduction of susceptible plant varieties, global trade in agricultural products, and changes in climatic conditions are responsible for aggravating the begomovirus problems during the last two decades. This review summaries th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 126 publications
(132 reference statements)
0
23
0
Order By: Relevance
“…Begomoviruses are the fastest co-evolving plant viruses and cause significant economic losses ( Jeske, 2009 ). Besides infecting the food, fiber, and weed plants ( Castillo-Urquiza et al, 2008 ), they have also been reported to infect the medicinal and aromatic plants and affect produce quality ( Saeed and Samad, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Begomoviruses are the fastest co-evolving plant viruses and cause significant economic losses ( Jeske, 2009 ). Besides infecting the food, fiber, and weed plants ( Castillo-Urquiza et al, 2008 ), they have also been reported to infect the medicinal and aromatic plants and affect produce quality ( Saeed and Samad, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, whitefly ( Bemisia tabaci Genn.) is a carrier of these begomoviruses that can affect diverse plant species such as crops, weeds, medicinal and aromatic plants [ 107 , 108 ]. Globally, the whitefly is a serious threat to many important plants due to the high invasiveness of the pest [ 109 , 110 ].…”
Section: Role Of Advanced Molecular Technologies For Better Utility Of a Conyzoidesmentioning
confidence: 99%
“…Viruses of the genus Begomovirus (family Geminividae ) are devastating pathogens that affect a variety of agronomic crops worldwide (Rojas et al, 2018). Begomoviruses are commonly associated with vegetables (Varma & Malathi, 2003) and have also been reported in medicinal and aromatic plants (Saeed & Samad, 2017). The genus Begomovirus has 388 species, which have importance by their worldwide distribution and their direct and negative impact over a wide range of crops (Zerbini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%